NYIT Energy Information Center. A first report - Magat, G. (New York Inst. of Tech., Old Westbury (USA). Center for Energy Policy and Research, 1976)
The Energy Information Center was created to serve (1) the research and information dissemination purposes of the Center for Energy Policy and Reearch, and (2) the information outreach programs of the Energy Advisory Service established by the Center. The Center is primarily concerned with (a) energy conservation, (b) alternative energy sources, (c) energy usage, and (d) energy policy, and insofar as they relate to these matters, it is concerned secondarily with fossil energy, nuclear energy, and international energy developments. Accordingly, the Energy Information Center acquires materials in such fields as engineering, economics, and the political, social, and behavioral sciences. In addition to serving the research and information dissemination needs of the Center for Energy Policy and Research, the Energy Information Center also supports the Center's Energy Advisory Service outreach program in which information and technical assistance in the use of energy conserving techniques and equipment is made available to industrial and commercial organizations, public officials, homeowners, and the general public throughout the New York New Jersey, and Connecticut area.